Neurophobia among family medicine specialist trainees in Malaysia - Chua, Leng Yien; Yahya, Normaskinah; Syed Khairuddin, Sharifah Hanim; Mohamad, Nor Faizah; Jaganathan, Pusparani; Hoo, Fan Kee; Wan Sulaiman, Wan Aliaa; Siew, Mooi Ching; Lee, Kai Wei (Association of South East Asian Nations, 2020)
Background: Neurophobia is defined as the fear of neural sciences and clinical neurology. Our study aims to determine the prevalence and factors associated with neurophobia among family medicine specialist trainees in Malaysia. Methods: A cross-sectional study was conducted among family medicine specialist trainees. Multiple logistic regression analysis was used to determine the factors associated with neurophobia. Results: A total of 415 subjects were enrolled into this study. The prevalence of neurophobia was 66% (n=274/415). In multivariate logistic regression analysis, having poor knowledge in neurology (odds ratio [OR] 3.85, 95% confidence interval [CI] 1.87-7.94), those with self-declared phobia toward neurology or neuroscience subject (OR 2.56 95% CI 1.30-5.03); those whose practice were in government sector (OR 1.78, 95% CI 1.09-2.88); those who perceived basic neuroscience (OR 1.95, 95% CI 1.03-3.67) and the complex clinical examination were important (OR 2.10, 95% CI 1.19-3.72); and those who perceived textbooks were not a useful method of learning (OR 1.78, 95% CI 1.05-3.02) were more prone to have neurophobia. Conclusion: Two-thirds of family medicine specialist trainees in Malaysia found neurology a difficult subject. Among the factors associated with neurophobia were those with poor knowledge in neurology, and those who self-declared to have phobia toward neurology or neuroscience subject.